PELAKSANAAN LAYANAN KAMAR OLEH ROOM ATTENDANT PADA MASA PANDEMI COVID-19 DI HOTEL GRAND ELITE PEKANBARU - Pradipta Pinkan Nastiwi; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The influence of Covid-19 has greatly impacted the world of hospitality, many hotels in Indonesia are currently experiencing a slump, including hotels in the city of Pekanbaru. One of the four-star hotels in the city of Pekanbaru is the Grand Elite Hotel Pekanbaru which is located at Jl. Riau, Riau Business Center Complex, Pekanbaru City. Hotel room cleanliness is the top priority and the best service. In this case the role of the room attendant is very important. Each room attendant job is carried out through certain established procedures. Therefore, this study aims to find out regarding the implementation of room service by the room attendant during the covid-19 period at the Grand Elite Pekanbaru hotel and what obstacles hinder the work of the room attendant in implementing room service at the Grand Elite Hotel Pekanbaru. This study uses a qualitative descriptive method to analyze problems based on data collection techniques in the form of observation, in-depth interviews, and documentation. Based on the results of research on the implementation of room service by room attendants during the covid-19 pandemic at the Grand Elite Pekanbaru hotel, it has gone well starting from managing rooms, serving guests, carrying out supervisor orders, collaborating with fellow friends in one section, collaborating with other sections. in one department, cooperate with other sections and other departments. But of course there are also obstacles in the implementation of room service by the room attendant itself such as the cleanliness of the linen which makes the room attendant's work speed not optimal, then the obstacle that is also often faced is cross-department work that is less than optimal but these obstacles can be overcome properly. Keywords: Hotel, Housekeeping Department, Room Attendant